1995
DOI: 10.1063/1.469322
|View full text |Cite
|
Sign up to set email alerts
|

Mass-resolved two-photon spectra of Kr2

Abstract: (2+1) resonantly enhanced multiphoton ionization spectra of jet-cooled Kr2 between ≊91 800 and 94 100 cm−1 have been recorded. Single isotopomer excitation spectra were obtained using time-of-flight mass detection. Vibronic structure for several Rydberg ← ground state transitions involving excited gerade states which dissociate to Kr+Kr* (4p55p) have been unambiguously analyzed for the first time, and molecular constants derived. Bond lengths were estimated from Franck–Condon calculations. These results compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Sawin et al have proven that hormone T3 diminishes in women over 80 years of age, and in men in their seventh decade of life (14). Harman et al found that the concentration of FT4 was significantly lower in elderly subjects, which is also consistent with the results of Lipson et al who showed that serum T4 levels were lower in women over the age of 60 but not in men (15). These data agree with our study in which we have shown that there is no statistically significant difference in the values of FT4 and FT3 hormones in women with thyroid dysfunction compared to women in the control group over 60 years.…”
Section: Discussionsupporting
confidence: 64%
“…Sawin et al have proven that hormone T3 diminishes in women over 80 years of age, and in men in their seventh decade of life (14). Harman et al found that the concentration of FT4 was significantly lower in elderly subjects, which is also consistent with the results of Lipson et al who showed that serum T4 levels were lower in women over the age of 60 but not in men (15). These data agree with our study in which we have shown that there is no statistically significant difference in the values of FT4 and FT3 hormones in women with thyroid dysfunction compared to women in the control group over 60 years.…”
Section: Discussionsupporting
confidence: 64%
“…To date, our group has provided detailed vibrational analyses of the single isotopomer spectra of Xe 2 , [9][10][11] Kr 2 , 10,12 KrXe, 13,14 and ArXe 14,15 which were recorded using ͑2ϩ1͒ REMPI/TOF experimental methods. We have for most of the transitions considered, also deduced excited state symmetries from separate REMPI/TOF spectra recorded with circularly polarized light, and excited state bond lengths from Franck-Condon factor calculations.…”
Section: Introductionmentioning
confidence: 99%
“…13 The most extensive studies of the gerade excited states of Kr 2 to date have been carried out by Dehmer and Pratt 14 and by Lipson and co-workers. 15 Both groups concentrated primarily on those dimer states in the vicinity of the Kr*(5p) manifold, and both used ͑2ϩ1͒ resonance enhanced multiphoton ionization ͑REMPI͒ and time-of-flight ͑TOF͒ mass spectrometry to obtain spectra. However, due to the superior mass resolution of their TOF mass spectrometer, the Canadian group 15 was able to obtain single isotopomer spectra, and, thus, determine unambiguous excited state vibrational numberings, and more accurate excited state molecular constants.…”
Section: Introductionmentioning
confidence: 99%
“…15 Both groups concentrated primarily on those dimer states in the vicinity of the Kr*(5p) manifold, and both used ͑2ϩ1͒ resonance enhanced multiphoton ionization ͑REMPI͒ and time-of-flight ͑TOF͒ mass spectrometry to obtain spectra. However, due to the superior mass resolution of their TOF mass spectrometer, the Canadian group 15 was able to obtain single isotopomer spectra, and, thus, determine unambiguous excited state vibrational numberings, and more accurate excited state molecular constants. Interestingly, Kr 2 *(5p) excited states are considerably shallower (D e ЈϷ120-620 cm Ϫ1 ) than those associated with the Kr*(5s) manifold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation